Taxonomy and phylogeny of Hypoxylon zhaotongensis sp. nov. (Hypoxylaceae, Xylariales), a bambusicolous fungus from Yunnan, China - Zhang, Gui-Qing; Dai, Dong-Qin; Wijayawardene, Nalin N.; Promputtha, Itthayakorn; Bhat, D. Jayarama; Dawoud, Turki M.; Tibpromma, Saowaluck; Wei, Xiao-Mei (Phytotaxa, 2023)
During a survey of bambusicolous fungi in Yunnan Province, southwestern China, several saprobic fungi associated with dead bamboo culms were collected and cursorily identified as species belonging to Xylariales (Sordariomycetes), based on a morphological approach. In this study, a new species, Hypoxylon zhaotongensis, from bamboo was established. In addition, molecular analyses based on multiple gene sequences (ITS, LSU, RPB2, β-tubulin) were carried out to determine the phylogenetic placement of the new isolates. The morphological characteristics show that our new taxon differs from the known Hypoxylon species in having broader asci and ascospores with conspicuously straight germ-slit, which is less than the spore length. Detailed description, photo-plate and a phylogenetic tree showing the taxonomic placement of the new species are provided in this paper.